THE POTENTIAL OF URONIDE HYDROCOLLOIDS FOR THE FORMATION OF SENSORY CHARACTERISTICS OF HEALTH PRODUCTS FROM HYDROBIONTS - T. Manoli; T. Nikitchina; A. Menchinska; Zh. Cui; Ya. Barysheva (Harčova Nauka ì Tehnologìâ, 2021)
The article presents the theoretical basis and practical aspects of the using of binary compositions of uronid polysaccharides in the technology of culinary products from aquatic organisms in jelly fillings. The relevance of the composition of natural high molecular weight polysaccharides, such as sodium alginate and low-esterified pectin, to promote the improvement of sensory characteristics of culinary products from aquatic organisms in the menu of fish restaurants is shown. The objectives of the study were to obtain a jelly filling of viscous consistency, followed by the formation of a stable, elastic gel for using in the technology of aquatic products. Obtaining a jelly filling involves det-ermining the parameters of the preliminary preparation of hydrocolloids; study of the influence of technological par-ameters on the sensory characteristics of the gel. Creating a dry mixture of sodium alginate and low-esterified pectin with salt and sugar was necessary to ensure the dispersion of particles of dry hydrocolloid powders to prevent sticking when swelling in water at a temperature of 18-20 ° C for 15 minutes. Intense swelling of the mixture occurs in the first 10 minutes of hydration.The degree of swelling reaches 5.8%; further increase in time has almost no effect on the swe-lling process. The swelling kinetics of the hydrocolloid mixture was evaluated by determining the tangent of the angle of inclination tangent to the curve describing the degree of swelling. The rational mass fraction of calcium ions for the formation of a transparent gel of stable, homogeneous, elastic consistency, which is 0.3-0.4% of the 10% solution of calcium chloride, was experimentally established. It was studied that dispersions with a mass fraction of a mixture of alginate: low-esterified pectin substances - 1.8% have a viscous consistency with a dynamic viscosity of less than 0.94 Pa • s, which is important for the implementation of technological operations of transportation and packaging of jelly fillings. The conditions and speed of gelation, which provide the finished culinary products with high sensory cha-racteristics and elastic consistency due to the regulated melting temperature, which is provided by the composition of uronide hydrocolloids, have been studied. It was found that the strength of the gel more than 140 g forms a mixture of hydrocolloids with a mass fraction of from 1.6 to 1.8%.